Effect of Atorvastatin on Glycaemic Parameters in Normoglycaemic and Prediabetic Subjects: A Prospective, Panel Study - Sansita Parida; Trupti Rekha Swain; Satya Narayan Routray; Rituparna Maiti (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Type 2 diabetes is associated with obesity and dyslipidemia, which are risk factor for cardiovascular disease. With recent FDA approved indications for statins being widened because of its lipid lowering and pleiotropic effects, statins are currently amongst the most widely used drugs in patients with or without diabetes. Although cardiovascular risk is reduced by statin therapy, its association with the development of diabetes is disputed. Aim: This study was conducted to evaluate the effect of Atorvastatin on glycaemic status of normoglycaemic and prediabetic individuals. Materials and Methods: An observational, prospective panel study was conducted on 75 subjects who were on Atorvastatin therapy. After baseline data collection and investigations, subjects were recruited depending on their glycaemic status into three groups: normoglycaemic, Impaired Fasting Glucose (IFG) and Impaired Glucose Tolerance (IGT) group. Atorvastatin therapy was continued and the subjects were followed every 6 months up to 18 months. At every follow up all glycaemic parameters were evaluated and subjects were assessed for continuation of statin therapy, dosing schedule and possible adverse drug reactions. Results: All three groups as a whole, irrespective of dose of Atrovastatin therapy, showed a statistically significant (p<0.0001) increase in all glycaemic parameters. In normoglycaemic group with low dose Atorvastatin, there was no significant change in 2-hour Post Prandial Blood Sugar (PPBS) but change in HbA1c% (p=0.0004) and FBS (p<0.0001) was significant, whereas, with high dose, changes in 2-hr PPBS and HbA1c % were significant from 6 months onwards. In IFG group, both with low and high dose of Atorvastatin, there was significant change in all glycaemic parameters from 12 months onwards. In case of IGT, especially with high dose Atorvastatin, significant changes were evident from 6 months onwards. Conclusion: Atorvastatin therapy especially with higher dose was found to be associated with glucose intolerance in normoglycaemics and also caused progression towards diabetes in prediabetic individuals.